Perceptions of the dimensions of the fairness of affirmative action: A pilot study - L. P. Vermeulen; M. Coetzee (South African Journal of Business Management, 2006)
The purpose of this study was to identify the dimensions of affirmative action (AA) fairness in order to develop a valid and reliable questionnaire to assess employees' perceptions of the fairness of AA decisions and practices, and to explore the relationship between employees' biographical characteristics and their perceptions of the dimensions of AA fairness. The research sample consisted of 349 participants connected to a large financial institution in South Africa. Principal axis factor analysis with a varimax rotation was performed on the data in order to uncover the different factors that employees perceived to be important for the fair and just management of affirmative action practices. Four factors define AA fairness: namely interactional, procedural (input), procedural (criteria) and distributive justice. One-way MANOVAs and associated ANOVAs revealed that the importance of the justice factors in AA fairness differed significantly across ethnicity and staff category. This study enables a better understanding of the dimensionality of AA fairness. It should ultimately contribute to more effective management of AA in the workplace.
Keywords: 650